The Role of Religious Education in Shaping Academic Ethics - Abdurahman Abdurahman; Diaz Dyda Giefhari; Faradiva Aritonang; Kanaya Akira; Eva Iryani (Sekolah Tinggi Agama Islam Sumatera Medan, 2026)
This study examines the role of religious education in shaping students’ academic ethics in higher education. The research is grounded in the growing concern over academic misconduct, such as plagiarism, cheating, and data manipulation, which reflects a gap between ethical ideals and academic practices. Using a qualitative approach, this study explores how religious values are internalized and implemented in academic contexts. The findings reveal that religious education plays a strategic role in fostering core ethical values, including honesty, responsibility, integrity, discipline, justice, and moral awareness. These values contribute significantly to guiding students’ academic behavior and strengthening their internal moral control. However, the study also identifies several challenges, such as the lack of curriculum integration, the dominance of theoretical teaching methods, weak role modeling, and the influence of digital technology and academic pressure. The novelty of this research lies in its integrative approach that connects religious values with concrete academic practices. This study contributes theoretically by enriching the discourse on academic ethics and practically by offering insights for developing value-based learning strategies in higher education.